Human parechovirus infection as an undiagnosed cause of adult pericarditis. Issue 6 (December 2017) - McGregor, Thomas; Bu'Lock, Frances A.; Wiselka, Martin; Tang, Julian W.
Graphical abstract: Highlights: Parechoviruses belong to the same virus family as rhinoviruses and enteroviruses. Human parechoviruses are well-recognised to cause neonatal and infant sepsis. Less is known about their contribution to older child and adult infection and disease. Human parechovirus myocarditis and pericarditis have now been described in adults. Commercial kits are now available to assist routine diagnostic testing for this virus.